Legal Analysis of Administratively Defective Certificates - Lumula, Yayuk; Darmawati, Darmawati; Sumiaty, Sumiaty (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
To achieve legal certainty and legal protection of land rights, a land rights certificate is given as proof of a person's ownership of land and its buildings. Land registration is carried out to ensure legal certainty. The aim of the research is to determine the procedures for canceling certificates belonging to administrative defects. This research uses a normative juridical method with a statutory regulatory approach. Research results found that the Certificate of Ownership was administratively flawed based on Minister of Agrarian Regulation No. 3 of 1999 article 1 number 12 states that the basis for canceling a certificate can be canceled because the decision is administratively flawed. administrative defects in the Certificate Issuance, the relevant Certificate may be submitted for Cancellation. Certificate cancellation can be done via BPN and TUN. In the process of issuing a certificate of land rights, there may be errors or administrative defects, so it can be canceled in three ways, namely Cancellation of land rights issued because there are administrative legal defects in the issuance of the decision to grant and/or certificate of land rights or implementing a court decision that has been made. obtain permanent legal force.